THE INFLUENCE OF THE PROBLEM BASED LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES IN SOCIAL STUDIES SUBJECT OF GRADE VIII AT STATE JUNIOR HIGH SCHOOL 3 P EMATANGSIANTAR - Rahmat Pauzi Butarbutar; Anggun Tiur Ida Sinaga; Tumpal Manahara Siahaan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of the Problem Based Learning (PBL) model on students' learning outcomes in the Social Studies (IPS) subject for Grade VIII at SMP Negeri 3 Pematangsiantar. The background of this research is based on the low learning outcomes of students, which are caused by the lack of active student involvement during the learning process. The PBL model was chosen because it emphasizes student involvement in solving real problems, which is expected to improve both understanding and learning outcomes. This research employs a quantitative approach with a quasi-experimental method. The research design used is the Nonequivalent Control Group Design involving two classes, namely class VIII-1 as the experimental group that applied the PBL model, and class VIII-2 as the control group that received conventional learning. Data collection techniques were carried out through pre-test and post-test. Instrument testing included validity, reliability, normality, homogeneity tests, and hypothesis testing using the Independent Samples t-Test with the assistance of SPSS version 26. The results of the study show that there is a significant difference in learning outcomes between students who were taught using the PBL model and those who were taught using conventional methods. The significance value in the t-test was 0.001 < 0.05, with the average N-Gain score of the experimental class being 44.67% and the control class being 31.24%. This indicates that the application of the PBL model has a significant effect on improving student learning outcomes.